Wiener Festwochen 1991. (Wien : Wiener Festwochen, 1991)
Rodtchenko ; Sedlacek, Franz ; Pontiller, Hans ; Radbruch, Thomas ; Kokoschka, Oskar ; Oberzill, Michael ; Fabre, Jan ; etc.
Wiener Festwochen 1991, Stadt Wien, 11. Mai - 16. Juni 1991
Duits
kunstcatalogus